AKU INGIN SEKOLAH; POTRET PENDIDIKAN DI KOMUNITAS MUSLIM MUALLAF SUKU BADUY BANTEN - Kiki Muhammad hakiki (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2015)
The focus of this research was to potray the phenomenon in field of education occured in Moslem muallaf Baduy community, especially in Islamic Education. From the result of this research, it was found that the quality of education in Baduy community was still very low. It was caused by some facts: firstly, it did not have enough teachers, the distribution of teachers around the area was not well-balanced, then the teachers got insufficient salary, next teachers still had low qualification and incompetence. Futhermore, the educational background of teachers and the real work application was not compatible, also, the implementation of the curriculum at school did not suitable with standarization of process and education mechanism. Another problem was the high percentage of people who do not continue their study and at last was the cultural restriction which did not allow their people or Baduy community to get formal education as well. Fokus dari penelitian ini adalah memotret fenomen dunia pendidikan yang terjadi di komunitas Baduy Muslim, khususnya dalam bidang pendidikan agama Islam. Dari hasil penelitian ditemukan fakta bahwa secara kualitas kondisi pendidikan di komunitas Baduy Muslim masih sangat rendah. Kondisi ini disebabkan oleh beberapa hal, diantaranya;persedian tenaga pendidik yang kurang, distribusi tidak seimbang, insentif para guru yang rendah, kualifikasi dibawah standar, guru-guru yang kurang kompeten, serta ketidaksesuaian antara kualifikasi pendidikan dengan bidang yang ditempuh, penerapan kurikulum di sekolah belum sesuai dengan mekanisme dan proses yang distandarkan. Permasalahan lainnya adalah angka putus sekolah juga masih relatif tinggi, dan yang terakhir, masih kuatnya aturan adat atau larangan adat yang melarang Orang Baduy untuk sekolah